2008
DOI: 10.1021/jp802347v
|View full text |Cite
|
Sign up to set email alerts
|

Classical Trajectory Study of the Dynamics of the Reaction of Cl Atoms with Ethane

Abstract: We present an electronic-structure and dynamics study of the Cl + C2H6 --> HCl + C2H5 reaction. The stationary points of the ground-state potential energy surface have been characterized using various electronic-structure methods and basis sets. Our best calculations, CCSD(T) extrapolated to the complete basis limit, using geometries and harmonic frequencies obtained at the MP2/aug-cc-pVTZ level, are in agreement with the experimental reaction energy. Ab initio information has been used to reparameterize a sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 43 publications
7
47
0
Order By: Relevance
“…Previous QCT calculations of the reaction of Cl atoms with methane 15 and with ethane 35,36 showed evidence for a chattering mechanism in which the light H atom moves repeatedly between the C and Cl atoms before forming products. All reactive trajectories were analysed for signatures of chattering 35 and a total of 154 trajectories showed this behaviour, 59 of which satisfied the above-mentioned criterion for sufficient ZPE in the products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous QCT calculations of the reaction of Cl atoms with methane 15 and with ethane 35,36 showed evidence for a chattering mechanism in which the light H atom moves repeatedly between the C and Cl atoms before forming products. All reactive trajectories were analysed for signatures of chattering 35 and a total of 154 trajectories showed this behaviour, 59 of which satisfied the above-mentioned criterion for sufficient ZPE in the products.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of product scattering angles (the scattering angle,  is defined as that between the velocity vectors of reagent Cl and product HCl in the COM frame), the translational energy of the products, and the internal energy of HCl were carried out as reported in our previous paper. 36 Our analysis of the internal energy of the radical product (CH3), however, incorporates additional calculation of the energy disposal into the normal modes of CH3. For the reactive trajectories, energy disposal in the nascent CH3 was determined by projecting its space-fixed cartesian velocities, ) (t q  , and coordinates, ) (t q , onto the 3N translational, rotational, and vibrational degrees of freedom of CH3 in its SRP-AM1 COM frame equilibrium geometry, ) (t eq q .…”
Section: Iiib: Analysis Of Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…From Eq. (6) the forms of the opacity function for the reactions of Cl atoms with neopentane and TMS can be derived, and the outcome (deduced to be the same for both reactions) is shown in Figure 11 Fully dimensional quasi-classical trajectory (QCT) calculations of the reaction of Cl atoms with ethane, 59 showed that the relationship in Eq. (5) did not apply well, however, and therefore the scattering could not be described simply by a hard sphere model for collisions.…”
Section: Centre Of Mass Frame Angular Scatteringmentioning
confidence: 98%
“…Cl + C 2 H 6 → C 2 H 5 + HCl (4) have been well studied both experimentally 17,18,22,[25][26][27]45 and computationally, [57][58][59][60][61] and the reactions of Cl atoms with propane 1,62-64 and n-butane 21,25,62 have been similarly investigated. The energetics and kinetics of these reactions are very similar to those for reactions (2) and (3); the reactions are all rapid and direct, have either a low or no barrier to reaction and the exothermicities of the primary hydrogen abstraction reactions are typically about -3 kcal mol -1 .…”
Section: Introductionmentioning
confidence: 99%